2015
DOI: 10.3109/14767058.2015.1035642
|View full text |Cite
|
Sign up to set email alerts
|

Early screening for critical congenital heart defects in asymptomatic newborns in Bursa province

Abstract: The diagnosis of coarctation of the aorta is missed in the newborns screened with pulse oximetry in the first 24-48 h after birth. Screening with pulse oximetry should be repeated for early diagnosis of coarctation of the aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
8
0
6
Order By: Relevance
“…The prevalence of CCHD in our study was 6 of 1000 live births, with positive CCHD screens occurring in 8/1452 (0.6%) of newborns. This was higher than previously reported in Sri Lanka 0.16% (14/8718), [ 13 ], India 0.16% (3/1855) [ 12 ], Turkey 0.12% (12/10,200) [ 18 ], Morocco 0.06% (5/8013) [ 19 ], the Netherlands 0.02% (5/23,959) [ 20 ], New Zealand 0.02% (3/16,644) [ 21 ], South Africa 0.01% (1/1001) [ 11 ] and the United States (US) 0.01% (1/6745) [ 16 ].…”
Section: Discussionmentioning
confidence: 55%
“…The prevalence of CCHD in our study was 6 of 1000 live births, with positive CCHD screens occurring in 8/1452 (0.6%) of newborns. This was higher than previously reported in Sri Lanka 0.16% (14/8718), [ 13 ], India 0.16% (3/1855) [ 12 ], Turkey 0.12% (12/10,200) [ 18 ], Morocco 0.06% (5/8013) [ 19 ], the Netherlands 0.02% (5/23,959) [ 20 ], New Zealand 0.02% (3/16,644) [ 21 ], South Africa 0.01% (1/1001) [ 11 ] and the United States (US) 0.01% (1/6745) [ 16 ].…”
Section: Discussionmentioning
confidence: 55%
“…Richmond et al 25 showed that repeat pulse oximetry brought their false positive rate down from 5% to 1%. In a local study from our country, Ozalkaya et al 26 reported the sensitivity and specificity of pulse oximetry screening in the diagnosis of CCHD as 60% and 99.9%, respectively. In the current study, sensitivity and specificity of the test were 83.3% and 99.9%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Although it has not been introduced by the Ministry of Health as a mandatory screening program in our country, many centers from our country continue to share their screening results. Ozalkaya et al reported the sensitivity and specificity of pulse oximetry screening in the diagnosis of critical congenital heart defects as 60.0 % and 99.9%, respectively (17). In a prospective study by Dilli et al in which they shared data from centers of 4 different levels in our country, they determined a sensitivity of 83.3%, a specificity of 99.9%, a positive predictive value of 11.9%, and a negative predictive value of 99.9% (18).…”
Section: Discussionmentioning
confidence: 99%